The Limits of Linked Suppression for Regulatory T Cells - Ito, Toshiro; Yamada, Akira; Batal, Ibrahim; Yeung, Melissa Y.; McGrath, Martina M.; Sayegh, Mohamed H.; Chandraker, Anil; Ueno, Takuya (Frontiers in Immunology, 2016)
Background: We have previously found that CD4+CD25+ regulatory T cells (T regs) can adoptively transfer tolerance after its induction with co-stimulatory blockade in a mouse model of murine cardiac allograft transplantation. In these experiments, we tested an hypothesis with three components: 1) the T regs that transfer tolerance have the capacity for linked suppression, 2) the determinants that stimulate the T regs are expressed by the indirect pathway, and 3) the donor peptides contributing to these indirect determinants are derived from donor MHC antigens. Methods: 1st heart transplants were performed from the indicated donor strain to B10.D2 recipients along with co-stimulatory blockade treatment (250μg i.p. injection of MR1 on day 0 and 250μg i.p. injection of CTLA-4 Ig on day 2). At least 8 weeks later a 2nd heart transplant was performed to a new B10.D2 recipient that had been irradiated with 450 cGy. This recipient was given 40 x 106 naïve B10.D2 spleen cells plus 40 x 106 B10.D2 spleen cells from the first (tolerant) recipient. We performed 3 different types of heart transplants with using various donor. Results: 1. T regs suppress the graft rejection in an antigen-specific manner. 2. T regs generated in the face of MHC disparities suppress the rejection of grafts expressing third party MHC along with tolerant MHC. Conclusion: The limits of linkage appear to be quantitative and not universally determined by either the indirect pathway or by peptides of donor MHC antigens.